Complete Basic Immunization Coverage Among Infants in Temanggung Regency - Sriatmi, Ayun; Martini, Martini; Agushybana, Farid; Jati, Sutopo Patria; Dewanti, Nikie Astorina Yunita; Handayani, Novia; Nandini, Nurhasmadiar (Universitas Aisyah Pringsewu, 2021)
Immunization is a process of forming immunity in individuals against infectious diseases. The government has required infants to be fully immunized, but in practice, it turned out that there were still many people refusing immunization. This study aimed to analyze the coverage and the punctuality of immunization and the factors that influenced it. The research was descriptive observational with qualitative and quantitative approaches. The population of the study was mothers who had less than 2 years old infants living in Temanggung Regency. 498 and 199 respondents were obtained in 2018 and 2019 by using a random sampling technique. The research instrument used was Rapid Card Check and MCH Handbook. The results showed that infants were not immunized (2-6,5%), and the punctuality of immunization was 32-89%. There was a relationship between knowledge (p=0,039) and the mother's perception (p=0,005) towards infants' essential immunization completeness.Imunisasi adalah proses pemberian kekebalan bagi individu dari suatu penyakit tertentu. Pemerintah telah mewajibkan balita untuk melakukan imunisasi dasar lengkap, namun pada praktiknya ternyata masih terdapat masuarakat yang enggan untuk imunisasi. Tujuan penelitian ini adalah untuk menganalisis cakupan dan ketepatan imunisasi, serta faktor-faktor yang mempengaruhinya. Metode yang digunakan dalam penelitian ini adalah deskriptif observasional dengan pendekatan kualitatif dan kuantitatif. Populasi penelitian adalah ibu yang memiliki balita dengan usia kurang dari 2 tahun yang tinggal di Kabupaten Temanggung. Dengan menggunakan teknik random sampling, diperoleh sebanyak 498 dan 199 responden pada tahun 2018 dan 2019. Instrumen penelitian yang digunakan adalah Rapid Card Check dan Buku KIA. Hasil menunjukkan bahwa terdapat balita yang tidak diimunisasi (2-6,5%) dan ketepatan imunisasi sebesar 32-89%. Terdapat hubungan antara pengetahuan (p=0,039) dan persepsi ibu (p=0,005) terhadap kelengkapan imunisasi dasar balita.